Concurrent large spontaneous portosystemic shunt embolization for the prevention of overt hepatic encephalopathy after TIPS: A randomized controlled trial. Issue 3 (15th April 2022) - Lv, Yong; Chen, Hui; Luo, Bohan; Bai, Wei; Li, Kai; Wang, Zhengyu; Xia, Dongdong; Guo, Wengang; Wang, Qiuhe; Li, Xiaomei; Yuan, Jie; Cai, Hongwei; et al.
Abstract: Background and Aims: Large spontaneous portosystemic shunt (SPSS) is associated with increased risk of HE in patients undergoing transjugular intrahepatic portosystemic shunt (TIPS). This study aimed to evaluate whether prophylactic embolization of large SPSS at the time of TIPS creation could reduce the incidence of post‐TIPS HE in patients with cirrhosis and variceal bleeding. Approach and Results: From June 2014 to August 2017, 56 patients with cirrhosis and large SPSS planning to undergo TIPS for the prevention of variceal bleeding were randomly assigned (1:1) to receive TIPS alone (TIPS group, n  = 29) or TIPS plus simultaneous SPSS embolization (TIPS+E group, n  = 27). The primary endpoint was overt HE. TIPS placement and SPSS embolization was successful in all patients. During a median follow‐up of 24 months, the primary endpoint was met in 15 patients (51.7%) in the TIPS group and six patients (22.2%) in the TIPS+E group ( p  = 0.045). The 2‐year cumulative incidence of overt HE was significantly lower in the TIPS+E group compared with the TIPS group (21.2% vs. 48.3%; HR, 0.38; 95% CI, 0.15–0.97; p  = 0.043). The 2‐year incidence of recurrent bleeding (TIPS+E vs. TIPS, 15.4% vs. 25.1%; p  = 0.522), shunt dysfunction (12.3% vs. 18.6%, p  = 0.593), death (15.0% vs. 6.9%, p  = 0.352), and other adverse events was not significantly different between the two groups. Conclusions: In patients with cirrhosis treated with TIPS for variceal bleeding, concurrent large SPSS embolization reduced the risk for overt HE without increasing other complications. Concurrent large SPSS embolization should therefore be considered for prophylaxis of post‐TIPS HE. Abstract : Large spontaneous portosystemic shunt (SPSS) is associated with increased risk of hepatic encephalopathy (HE) in patients undergoing transjugular intrahepatic portosystemic shun (TIPS). This randomized controlled trial aimed to evaluate whether prophylactic embolization of large SPSS at the time TIPS creation could reduce the incidence of post‐TIPS HE in patients with cirrhosis and variceal bleeding. From June 2014 to August 2017, 56 patients with cirrhosis and large SPSS planning to undergo elective TIPS for the prevention of variceal bleeding were randomly assigned (1:1) to receive TIPS alone (n=29) or TIPS plus simultaneous SPSS embolization (n=27). Results of this study showed that in patients with cirrhosis treated with TIPS for variceal bleeding, concurrent large SPSS embolization reduced the risk for overt HE without increasing other complications.